A Dangerous life (Shuiyi Investment Private for and on behalf of Keenan CV, 1988)
The Philippine EDSA revolution comes vividly to life in this epic that dramatizes the turbulent events leading to the downfall of the Marcos dictatorship and the elevation of Corazon Aquino to power, featuring an American journalist reporting in Manila, 1983-1986.